Subcallosal cingulate deep brain stimulation for treatment-resistant depression: a multisite, randomised, sham-controlled trial. (November 2017) - Holtzheimer, Paul E; Husain, Mustafa M; Lisanby, Sarah H; Taylor, Stephan F; Whitworth, Louis A; McClintock, Shawn; Slavin, Konstantin V; Berman, Joshua; McKhann, Guy M; Patil, Parag G; Rittberg, Barry R; Abosch, Aviva; et al.
Summary: Background: Deep brain stimulation (DBS) of the subcallosal cingulate white matter has shown promise as an intervention for patients with chronic, unremitting depression. To test the safety and efficacy of DBS for treatment-resistant depression, a prospective, randomised, sham-controlled trial was conducted. Methods: Participants with treatment-resistant depression were implanted with a DBS system targeting bilateral subcallosal cingulate white matter and randomised to 6 months of active or sham DBS, followed by 6 months of open-label subcallosal cingulate DBS. Randomisation was computer generated with a block size of three at each site before the site started the study. The primary outcome was frequency of response (defined as a 40% or greater reduction in depression severity from baseline) averaged over months 4–6 of the double-blind phase. A futility analysis was performed when approximately half of the proposed sample received DBS implantation and completed the double-blind phase. At the conclusion of the 12-month study, a subset of patients were followed up for up to 24 months. The study is registered at ClinicalTrials.gov, number NCT00617162 . Findings: Before the futility analysis, 90 participants were randomly assigned to active (n=60) or sham (n=30) stimulation between April 10, 2008, and Nov 21, 2012. Both groups showed improvement, but there was no statistically significant difference in response during the double-blind, sham-controlled phase (12 [20%] patients in the stimulation group vs five [17%] patients in the control group). 28 patients experienced 40 serious adverse events; eight of these (in seven patients) were deemed to be related to the study device or surgery. Interpretation: This study confirmed the safety and feasibility of subcallosal cingulate DBS as a treatment for treatment-resistant depression but did not show statistically significant antidepressant efficacy in a 6-month double-blind, sham-controlled trial. Future studies are needed to investigate factors such as clinical features or electrode placement that might improve efficacy. Funding: Abbott (previously St Jude Medical).